Di bronzo e d’argento: sculture del Settecento italiano nella magnifica Patriarcale di Lisbona - Vale, Teresa Leonor. M. (2012)
King Giovanni V of Portugal undoubtedly admired Italian marble sculptures; in fact he had had the contents of the basilica of Mafra enriched with them. In spite of this fact, for his Patriarchal Basilica in Lisbon he had chosen metal decorations. Besides the numerous silver works made in Rome, we know of the existence in the Patriarchal of two high quality sculptures, which had been greatly admired at that period; they were a relief portraying the Virgin with Child in gilded bronze (armolu) for the façade of the basilica and inside the latter a gilded silver statue of the Immaculate Mary. This statue was particularly admired in Rome as well as in Lisbon. Both statues disappeared during the terrible period of destruction which the Portuguese capital underwent on the first of November 1755. These two sculptures represent only a very small part of Giovanni V's dream of taking some pieces of Roman art to Lisbon, the art he admired so much from afar and dreamt of visiting personally. Being unable to realize this wish the king tried to experience it by means of the numerous works of art which he acquired during his life and his long reign.